A ceramic/polymer composite solid electrolyte for sodium batteries. Issue 41 (6th October 2016) - Zhang, Zhizhen; Zhang, Qiangqiang; Ren, Cheng; Luo, Fei; Ma, Qiang; Hu, Yong-Sheng; Zhou, Zhibin; Li, Hong; Huang, Xuejie; Chen, Liquan
Abstract : A solvent-free ceramic/polymer composite solid electrolyte has been proposed and demonstrated well in solid-state Na batteries for the first time. Abstract : Achieving high ionic conductivity in solid electrolytes and reducing the interfacial resistance between solid electrolytes and electrode materials are considered to be one of the biggest challenges in developing solid-state batteries. The integration of the high ionic conductivity of inorganic ceramics and the flexibility of organic polymers was attempted to yield a solvent-free ceramic/polymer composite solid electrolyte for Na batteries for the first time. The composite solid electrolytes exhibit a Na + ion conductivity as high as 2.4 mS cm −1 at 80 °C. Meanwhile, this composite membrane is thermally stable up to 150 °C and maintains the flexibility of polymer electrolytes. The solid-state Na3 V2 (PO4 )3 /CPE/Na battery using this ceramic/polymer composite electrolyte exhibits an initial reversible capacity of 106.1 mA h g −1 and excellent cycle performance with negligible capacity loss over 120 cycles.